Scoping review of echocardiographic parameters associated with diagnosis and prognosis after resuscitated sudden cardiac arrest. (March 2023) - Liu, Linda; Karatasakis, Aris; Kudenchuk, Peter J.; Kirkpatrick, James N.; Sayre, Michael R.; Carlbom, David J.; Johnson, Nicholas J.; Probstfield, Jeffrey L.; Counts, Catherine; Branch, Kelley R.H.
Abstract: Aim: Current international guidelines recommend early echocardiography after resuscitated sudden death despite limited data. Our aim was to analyze published data on early post-resuscitation echocardiography to identify cardiac causes of sudden death and prognostic implications. Methods: We reviewed MEDLINE, EMBASE, and CENTRAL databases to December 2021 for echocardiographic studies of adult patients after resuscitation from non-traumatic sudden death. Studies were included if echocardiography was performed <48 hours after resuscitation and reported (1) diagnostic accuracy to detect cardiac etiologies of sudden death or (2) prognostic outcomes. Diagnostic endpoints were associations of regional wall motion abnormalities (RWMA), ventricular function, and structural abnormalities with cardiac etiologies of arrest. Prognostic endpoints were associations of echocardiographic findings with survival to hospital discharge and favorable neurological outcome. Results: Of 2877 articles screened, 16 (0.6%) studies met inclusion criteria, comprising 2035 patients. Two of six studies formally reported diagnostic accuracy for echocardiography identifying cardiac etiology of arrest; RWMA (in 5 of 6 studies) were associated with presumed cardiac ischemia in 17–89% of cases. Among 12 prognostic studies, there was no association of reduced left ventricular ejection fraction with hospital survival (v10) or favorable neurologic status ( n  = 5). Echocardiographic high mitral E/e′ ratio ( n  = 1) and right ventricular systolic dysfunction ( n  = 2) were associated with poor survival. Conclusion: This scoping review highlights the limited data on early echocardiography in providing etiology of arrest and prognostic information after resuscitated sudden death. Further research is needed to refine the clinical application of early echocardiographic findings in post arrest care.